Crypto Market Experience: Navigating Regulatory Challenges in Modern Conditions - Volkova, Yuliia; Bon, Bohdan; Borysenko, Anton; Leheza, Yuliia; Leheza, Yevhen (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
The legal regulation of digital finance is at an initial stage. It has been proven that many countries are favorable to the full or partial recognition of cryptocurrency as a means of payment, among them: Spain - the official payment system; Germany - monetary unit and form of private money; USA - currency, form of money, Sweden - contractual means of payment; the object of money transfers in certain states, Canada - a means of calculation, etc. It has been established that in Ukraine, the conservative nature of legal regulation of financial relations is considered in the context of implementing digital financial technologies given the task of protecting both public interests and the interests of individuals. Conclusions have been made, first, the issue of legal evaluation of cryptocurrencies is still not finally resolved and their legal nature also remains debatable; second, cryptocurrencies being alternative settlement units pose a threat to the dominance of public currencies, as they enable competition between private financial agents and states; third, according to its essence, electronic money is a kind of electronic promissory note.